Phage capsid protein-directed MnO2 nanosheets with peroxidase-like activity for spectrometric biosensing and evaluation of antioxidant behaviour. Issue 37 (26th April 2017) - Han, Lei; Liu, Pei; Zhang, Haijiao; Li, Feng; Liu, Aihua
Abstract : The phage capsid protein pVIII-directed MnO2 nanosheets (NSs) with peroxidase-like activity are synthesized for biosensing and evaluation of antioxidant behaviour. Abstract : Small molecular weight proteins (5.21 kDa) were used as bio-templates to synthesize MnO2 nanosheets (NSs). This work will open up a protein-directed avenue to synthesize 2D morphology. Further, the as-prepared MnO2 NSs showed intrinsic peroxidase-like activity and were then applied for glucose detection and evaluation of antioxidant behaviours of typical antioxidants.